2021
DOI: 10.1097/opx.0000000000001785
|View full text |Cite
|
Sign up to set email alerts
|

Agreement and Repeatability of Corneal Thickness and Radius among Three Different Corneal Measurement Devices

Abstract: SIGNIFICANCE:Corneal refractive surgery screening, orthokeratology, and contact lens fitting require accurate estimation of the corneal thickness and curvature. We found that any of the imaging devices used in this study can be used to image a healthy myopic cornea, which is essential to screen for corneal ectasia. PURPOSE: This study aimed to compare agreement and repeatability of corneal thickness and radius measurements obtained using Scheimpflug imaging (Pentacam HR), swept-source optical coherence tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 28 publications
8
17
0
Order By: Relevance
“…Previous studies [16,[18][19] on healthy eyes obtained average values of TCT between 530 and 550 µm with AS-OCT, which are comparable to the reported average of 531.85 ± 34.08 µm in this study. The repeatability of TCT measurements with MS-39 was improved compared with the reported CASIA SS-1000 measurements in the literature [18,19]. Savini et al [16] evaluated the repeatability of TCT measurements with MS-39, acquiring a CoR of 4.77 µm, a CoV of 0.32%, and an ICC of 0.999.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Previous studies [16,[18][19] on healthy eyes obtained average values of TCT between 530 and 550 µm with AS-OCT, which are comparable to the reported average of 531.85 ± 34.08 µm in this study. The repeatability of TCT measurements with MS-39 was improved compared with the reported CASIA SS-1000 measurements in the literature [18,19]. Savini et al [16] evaluated the repeatability of TCT measurements with MS-39, acquiring a CoR of 4.77 µm, a CoV of 0.32%, and an ICC of 0.999.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of CCT measurement, excellent repeatability was con rmed by the small COR (1.94µm) and CoV (0.131%) scores and the ICC of 0.9996 from the current study. Measurements of CCT from MS-39 produced mean values (535.99 ± 34.17 µm) comparable to those previously reported using SS-OCT on healthy eyes [18][19][20][21][22][23]. Previous studies on myopic eyes showed that Pentacam HR rotating Scheimp ug camera and Sirius Scheimp ug camera-Placido topographer (CSO, Scandicci, FI, Italy) achieved inferior repeatability [24][25][26].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Moreover, there is currently no consensus, if different technologies, such as OCT, Scheimpflug or ultrasound, when assessing corneal thickness, are interchangeable or if conversion factors are applicable. Several reports demonstrated a higher measured corneal thickness by RSC compared to OCT devices [ 24 , 38 , 39 ], whereas interchangeability is reported as well [ 40 ]. These discrepancies might be due to the different investigated populations and dependent on age and the presence of ocular pathologies [ 41 ].…”
Section: Discussionmentioning
confidence: 99%